2001
DOI: 10.1046/j.1365-2265.2001.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and growth hormone (GH) secretagogue receptor (GHSR) mRNA expression in human pituitary adenomas

Abstract: Ghrelin mRNA, in addition to GHSR mRNA, is expressed in various types of pituitary adenoma with different levels of expression in each type. Our findings suggest that ghrelin produced in pituitary adenoma may play some role in the mechanism underlying the development of adenoma cells through autocrine and/or paracrine pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
49
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 39 publications
7
49
2
1
Order By: Relevance
“…Our finding may link circulating or locally produced ghrelin to pituitary tumorigenesis via an autocrine/paracrine pathway. Indeed, ghrelin mRNA is expressed in pituitary tumours with the highest levels in non-functioning pituitary adenomas; however, the level of ghrelin mRNA expression did not correlate with tumour size or with the grading of the tumours (17,23). It has been demonstrated that GHS-R1a mRNA expression is increased in some somatotroph tumours, suggesting that the receptor may be a promoting factor in tumorigenesis (17,24).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding may link circulating or locally produced ghrelin to pituitary tumorigenesis via an autocrine/paracrine pathway. Indeed, ghrelin mRNA is expressed in pituitary tumours with the highest levels in non-functioning pituitary adenomas; however, the level of ghrelin mRNA expression did not correlate with tumour size or with the grading of the tumours (17,23). It has been demonstrated that GHS-R1a mRNA expression is increased in some somatotroph tumours, suggesting that the receptor may be a promoting factor in tumorigenesis (17,24).…”
Section: Discussionmentioning
confidence: 99%
“…Two of 13 pediatric cases studied by RT-PCR contained the specific GHS-R 1a mRNA and approximately half of the cases had that of GHS-R 1b. Far from having demonstrated a direct (possibly autocrine or paracrine) mechanism of ghrelin in lung cells, the presence of the specific receptor in at least a fraction of cases may indicate that ghrelin not only regulates GH release at the central level but may also exert other functions in peripheral tissues via specific receptors, as also shown in the gastroenteropancreatic tract Volante et al 2002) and in pituitary adenomas (Kim et al 2001;Korbonits et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin has subsequently been localized in the pituitary gland, arcuate nucleus of the hypothalamus, kidney, and placenta (Kojima et al 1999;Date et al 2000;Mori et al 2000;Gualillo et al 2001). Some tumors were also found to produce ghrelin, i.e., pituitary adenomas, gastrointestinal carcinoids, and endocrine tumors of the pancreas (Kim et al 2001;Korbonits et al 2001;Papotti et al 2001;Volante et al 2002).…”
mentioning
confidence: 99%
“…Previous studies investigating ghrelin and GHSR expression in pituitary adenomas have produced conflicting results (3,6,8), and data showing the correlation between ghrelin and GHSR expression levels and the clinical features of pituitary adenomas are limited. The aim of the present study, therefore, was to examine the mRNA and protein expression levels of ghrelin and GHSR in a full spectrum of human pituitary adenoma subtypes, as well as normal pituitary tissue, and…”
Section: Introductionmentioning
confidence: 97%
“…Human GHSR contains two subtypes, type 1a (GHSR-1a) and type 1b (GHSR-1b), with the latter being 77 amino acids shorter than the former. Generally, GHRS-1a binds and responds to GHS, while GHRS-1b is biologically inactive (3).…”
Section: Introductionmentioning
confidence: 99%